High-quality reference plastomes in Tillandsia species living at the dry limits - Kiefer, Christiane; Buchmann, David; Koch, Marcus (Plant systematics and evolution, 2024)
Ongoing climate change has had severe impacts on biota worldwide, including plants and especially those with narrow ecological niches that have adapted to extreme environments for several hundred thousand of years. Several members of the genus Tillandsia are known for their ability to live at the dry limits of life in the Atacama Desert and have potential as bioindicators for climate change at the Pacific Ocean and adjacent ecosystems. However, genomic information on these plants is scarce. In this study, five complete plastid genomes of two Tillandsia species were de novo assembled at very high quality using DNA sequence data from a combination of next-generation short-read and Sanger sequencing. The newly assembled and fully annotated plastid genomes had an average length of 156,319 base-pairs with the typical highly conserved quadripartite circular structures. Gene order and content were highly conserved, with the exception of the variable gene ycf1. The newly assembled plastid genomes were placed into a broader phylogenetic context to check the quality of sequence data obtained from past approaches relying on reference-based assemblies. It is shown that earlier presented Tillandsia plastomes are either not of sufficient quality or lack any metadata. The herein presented reference plastomes will guide future research to study parallel and convergent evolution in a reliable evolutionary framework and will allow the use of plastome data with little genetic variation for population genomics studies in species such as Tillandisa landbeckii with prevailing clonal propagation.